Metal Ion-Based Supramolecular Self-Assembly for Cancer Theranostics - Chen, Bing; Chu, Chengchao; Ren, En; Lin, Huirong; Zhang, Yang; Wang, Peiyu; Yao, Hong; Liu, Ailin; Liu, Gang; Lin, Xinhua (Frontiers in Chemistry, 2022)
Metal-ion-based self-assembly supramolecular theranostics exhibit excellent performance in biomedical applications owing to their potential superiorities for simultaneous precise diagnosis, targeted drug delivery, and monitoring the response to therapy in real-time. Specially, the rational designed systems could achieve specific in vivo self-assembly through complexation or ionic interaction to improve tissue-specific accumulation, penetration, and cell internalization, thereby reducing toxicities of drugs in diagnostics and therapy. Furthermore, such imaging traceable nanosystems could provide real-timely information of drug accumulation and therapeutic effects in a non-invasive and safe manner. Herein, the article highlights the recent prominent applications based on the metal ions self-assembly in cancer treatment. This strategy may open up new research directions to develop novel drug delivery systems for cancer theranostics.